Proceedings of the Proceedings of the 1st International Multi-Disciplinary Conference Theme: Sustainable Development and Smart 2020
DOI: 10.4108/eai.28-6-2020.2298232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding turmeric powder to local buck rabbit’s rations on some production and blood traits

Abstract: Male rabbits are tested when turmeric powder was added to their daily food over 4-5 weeks. The food consists of 15.8% crude protein including 2865.5 Kcal/ Kg metabolizable energy. The test was carried over three sets of 10 rabbits. The turmeric was fed under a control process of 4 or 8 gram/kg. These groups are classified into T1: without adding nothing, including T2 and T3 with added turmeric with 4 and 8 gram/Kg respectively. The biochemical blood parameters of slaughtered rabbits are investigated and studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
2
1
0
Order By: Relevance
“…Pujiawati et al (2021) showed that addition of 1.5% turmeric powder enhanced growth performance including final BW, BWG, FI and FCR in growing rabbits. These findings are in accordance with Abd EL-Latif et al, 2019;El-Rawi et al, 2020. El-Rawi et al (2020 concluded that administration of turmeric powder (4 and 8 g/kg feed) had a positive impact on final BW, BWG, FI, and FCR.…”
Section: Moringa Oleiferasupporting
confidence: 91%
“…Pujiawati et al (2021) showed that addition of 1.5% turmeric powder enhanced growth performance including final BW, BWG, FI and FCR in growing rabbits. These findings are in accordance with Abd EL-Latif et al, 2019;El-Rawi et al, 2020. El-Rawi et al (2020 concluded that administration of turmeric powder (4 and 8 g/kg feed) had a positive impact on final BW, BWG, FI, and FCR.…”
Section: Moringa Oleiferasupporting
confidence: 91%
“…The decrease of the reaction time in treated groups could be considered as good indication for the higher sexual activity and the more secretion of testosterone hormone. The achieved findings agree with those of El-Rawi et al (2020) which revealed that the sexual libido decreased significantly in V-line rabbit bucks, receiving turmeric at 4 and 8 g/kg diet than those of the control group. Similarly, the findings of Abd El-hameed Noura and Heshmat (2019) showed that the semen characteristics of rabbit bucks administrated with ginger 200 and 250 mg/kg/BW increased significantly than those of the control group.…”
Section: Semen Characteristicssupporting
confidence: 89%
“…Moreover, Kaegon et al [83] revealed that supplementing the growing rabbit diet with turmeric at the levels of 0.5-0.9 g per kg of the diet resulted in beneficial effects on serum metabolites, particularly creatinine, glucose, urea, cholesterol, conjugated bilirubin, total bilirubin, albumin, and total protein. El-Rawi et al [84] stated that turmeric powder (4-8 g/kg of diet) could improve rabbit growth, digestibility, and some carcass traits. Furthermore, it enhanced immunity and served as an exogenous antioxidant.…”
Section: Turmericmentioning
confidence: 99%